Association of Zinc Concentration in Seminal Plasma and Blood with Several Parameters of Semen in Infertile Males - Anum Saeedullah, Summeira Jabeen Shah, Hina Hakim, Asma Farid4, Sikandar Ali Khan, Sudhair Abbas Bangash, Nabiha Naeem, Umar Amin Malhi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the concentration of zinc inthe blood and seminal plasma with semen parameters between fertile and infertile males Methodology: This prospective study was carried out in the Department of Biochemistry, Hayatabad medical complex, Peshawar. Fifty (50)infertile males, not receiving any treatment and had regularintercourse for 1 yearaged 25-45 years were selected from HMC. They were divided into 35oligospermia and 15 azoospermic. 35 fertile males were nominatedamongthe overallresidents and were taken as the control group after their semen analysis was taken as normozoospermic. According to WHO criteria semen is analyzed. With the help of 5br Serum and seminal plasma zinc were estimated. Result: There was a significant difference found in serum and seminal levels of zinc in normozoospermic, oligospermia (p less than 0.05), and azoospermic (p-value less than 0.05) individuals. The correlation of seminal plasma zinc with sperm counts showed a positive association with the count of sperm and a negative association with motility of sperm in normozoospermic/oligospermia and a negative association of concentration with pH, and volume, WBC in all groups. No association was found with the morphology of sperm. Conclusion: It has been concluded that zinc interfered with fertility by having a considerable impact on many semen parameters. It suggests that measuring seminal plasma zinc could be useful for diagnosing and treating male infertility.